2021
DOI: 10.1007/s00277-021-04704-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with multiple myeloma harboring chromosome 1q gain/amplification in the era of modern therapy

Abstract: Chromosome 1q gain/amplification (1q +) has been reported to be associated with inferior outcomes in multiple myeloma (MM) patients. Big therapeutic advances have shifted the treatment landscape by introducing monoclonal antibodies. There is a relative lack of data on outcomes in patients harboring this alteration in the era of monoclonal antibodies. Baseline characteristics and therapy-related data from newly diagnosed MM patients harboring 1q + detected by fluorescence in situ hybridization (FISH) were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…We report a real-world retrospective study of the prognosis and efficacy of 1q21 gain in patients with newly diagnosed multiple myeloma who received bortezomib-based chemotherapy. We found that 1q21 gain is common (45.9%) at diagnosis in multiple myeloma, and this aberration is associated with later ISS stage levels, lower serum albumin levels, and elevated LDH concentrations, consistent with previous research results ( 3 , 8 , 16 ). Moreover, we further demonstrated the prognostic risk value of 1q21 gain in PFS and OS in MM patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We report a real-world retrospective study of the prognosis and efficacy of 1q21 gain in patients with newly diagnosed multiple myeloma who received bortezomib-based chemotherapy. We found that 1q21 gain is common (45.9%) at diagnosis in multiple myeloma, and this aberration is associated with later ISS stage levels, lower serum albumin levels, and elevated LDH concentrations, consistent with previous research results ( 3 , 8 , 16 ). Moreover, we further demonstrated the prognostic risk value of 1q21 gain in PFS and OS in MM patients.…”
Section: Discussionsupporting
confidence: 92%
“…Highrisk copy number gains of 1q21 partly originate from the hypomethylation of 1q12 pericentromeric heterochromatin (7). Nevertheless, the prognostic value of chromosome 1q21 aberrations is still controversial among cytogenetic abnormality studies (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…11 A recent report found no prognostic benefit of daratumumab-based therapy on the outcome of 1q21+ newly diagnosed MM patients in a real-world setting, though this study has limitations because of its relatively small sample size and its retrospective, single-center nature. 12 Overexpression of complement regulatory proteins CD55 and CD59 has been implicated in daratumumab resistance. 13 Interestingly, the gene encoding CD55 is localized to 1q32.2, and overexpression of CD55 has been suggested to contribute to daratumumab resistance in 1q21+ patients.…”
mentioning
confidence: 99%
“… 11 A recent study found no prognostic benefit of daratumumab-based therapy on the outcome of newly diagnosed MM patients with 1q21+ in a real-world setting, although the study had limitations because of its relatively small sample size and its retrospective, singlecenter nature. 12 …”
mentioning
confidence: 99%
“…However, data supporting the effectiveness of adjunctive daratumumab in 1q21 + patients are scarce, since pivotal trials didn’t report outcomes on this patient population, and potential mechanisms of resistance conferred by 1q21 + to daratumumab therapy have been proposed [ 1 ]. Interestingly, Hu and colleagues [ 9 ] have recently published a retrospective study describing real-world outcomes of 34 NDMM patients harboring 1q21 + , reporting no prognostic role of daratumumab therapy and worse outcomes for amp1q patients compared to gain1q patients. As the authors noted, only one study by Mohan and colleagues [ 10 ] had previously investigated the outcomes of 1q21 + patients treated with daratumumab, reporting poor prognosis associated with both 1q21 + and GEP-70 HR status, although patients in that study were heavily pretreated and only 63% of them received daratumumab in combinations with immunomodulatory drugs.…”
mentioning
confidence: 99%